Rehabilitation with zygomatic implants: a treatment option for the atrophic edentulous maxilla--9-year follow-up. - Kuabara, Marcos Rikio; Ferreira, Edilson José; Gulinelli, Jéssica Lemos; Paz, Luis Guillermo Peredo (My University, 2010)
This article reports the 9-year clinical outcome of the two-stage surgical rehabilitation of a severely atrophic edentulous maxilla with a metal-resin fixed denture supported by implants anchored in the zygomatic bone and the maxilla. After clinical and radiographic examination, zygomatic implants were inserted bilaterally and four standard implants were placed in the anterior region of the maxilla. Six months later, the implants were loaded with a provisional acrylic resin denture, and the definitive implant-supported metal-resin fixed denture was provided 1 year after implant placement. After 9 years of follow-up, no painful symptoms, peri-implant inflammation or infection, implant instability, or bone resorption was observed. In the present case, the rehabilitation of severe maxillary atrophy using the zygomatic bone as a site for implant anchorage provided good long-term functional and esthetic results. Therefore, with proper case selection, correct indication, and knowledge of the surgical technique, the use of zygomatic implants associated with standard implants offers advantages in the rehabilitation of severely resorbed maxillae, especially in areas with inadequate bone quality and volume, without needing an additional bone grafting surgery, thereby shortening or avoiding hospital stay and reducing surgical morbidity.
Keywords: alveolar bone loss; case report; denture; edentulousness; follow up; human; jaw disease; male; maxilla; methodology; middle aged; tooth implantation; zygoma; Alveolar Bone Loss; Dental Implantation, Endosseous; Denture, Overlay; Follow-Up Studies; Humans; Jaw, Edentulous; Male; Maxilla; Maxillary Diseases; Middle Aged; Zygoma